Secular Students in a Religious Environment. Oslo-Students on Internship in Africa - Geir Hoaas (European Teacher Education Network, 2016)
Early Childhood students may participate in a 3 months internship in 3 African countries. We have challenged a group of students from the last 5 years of the program to respond to how they experienced the religious atmosphere in and outside the kindergartens. Although their own home country has a strong Christian heritage, the present-day society is rather secularized, and religious vocabulary is not common in everyday speech. The contrast to the African countries is striking. They encounter a clearly verbalized religious upbringing in the kindergartens, even to the point where religious faith becomes part of the discipline. How did they react to these experiences, as well as to the many personal questions about their own faith? We describe and analyze these responses.